EKSISTENSI BAHASA INDONESIA SEBAGAI JATI DIRI BANGSA DI ERA DIGITAL DAN GLOBALISASI - Zahratul Aini Lubis; Zamasri Raudhah; Tasya Dwita Br Tampubolon; Zahirah Defan; Ita Khairani; Zaman Suherman Sinambela; Ventura Manik (STKIP Subang, 2026)
Indonesian plays a crucial role as a national identity, a unifying language, and an official means of communication within society. However, the rapid development of digital technology and globalization has created significant challenges to its existence, particularly through the increasing influence of foreign languages, slang expressions, digital abbreviations, and code-mixing practices among younger generations. This study aims to examine the challenges faced by the Indonesian language as a symbol of national identity in the digital and global era and to identify adaptive strategies for maintaining its sustainability. The research employed a qualitative descriptive approach through a literature review. Data were collected from scientific journals, academic articles, books, and other relevant references discussing language development in the context of digitalization and globalization. The findings indicate that digitalization and globalization have both positive and negative impacts on the Indonesian language. On the one hand, technological advancements provide opportunities for wider dissemination and development of the language. On the other hand, they contribute to the declining use of standard Indonesian, the growing influence of foreign languages, and a reduced sense of linguistic pride among some speakers. Therefore, strengthening digital literacy, promoting contextual language awareness, innovating Indonesian language education, and utilizing digital media as a platform for language promotion are essential efforts. These strategies are expected to ensure that Indonesian remains relevant, adaptive, and resilient as a representation of national identity amid global transformations.